Drug Patch Test as a Diagnostic Test to Determine the Culprit Drug of Cutaneous Adverse Drug Reaction (CADR) - Damayanti; Hari Sukanto; Marsudi Hutomo; Sylvia Anggraeni; Menul Ayu Umborowati; Cita Rosita Sigit Prakoeswa (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Cutaneous Adverse Drug Reaction (CADR) is a frequent problem in clinical practice since there were new drugs or drug misuse, which leads to high morbidity and mortality rate. It is often difficult to determine the offending drug only from the history. Provocation test, intradermal test or skin prick test are of significant value, but having higher risk to re-precipitate life-threatening reaction. Drug patch test (DPT) is a test, which is performed to CADR patient to determine the culprit drug. The main advantages of DPT are, it gives rarely adverse reaction and any commercialized form of drugs can be used.Methods: This is a retrospective study, aimed to analize the clinical relevance between anamnesis and DPT result in patient with history of CADR. All patient, who were performed with DPT in one year period in Dr. Soetomo General Academic Hospital Surabaya Indonesia, were evaluated in this study. Results: There were 14 patients with history of CADR, who performed DPT; consist of 7 maculopapular eruption cases, 4 Stevens-Johnson Syndrome (SJS) cases, 1 Fixed Drug Eruption (FDE) case, 1 Acute Generalized Exanthematous Pustulosis (AGEP) case and 1 Drug Reaction with Eosinophilia and Systemic Reaction (DRESS) case. There were 9 patients (64.3 %), who got positive result of DPT. The relevance between anamnesis and positive result of DPT were shown in 8 patient (88.9%) of 9 patient with positive DPT result. Conclusion: DPT has important role in identifying the culprit drug in CADR, especially when multiple drugs are involved.